An Analysis of the Influence of ESG Rating Divergence on Investor Sentiment - Liao, Yu; Wu, Ying (International Journal of Global Economics and Management, 2024)
The global financial markets have experienced a significant development with the emergence of the notions of "sustainable development" and "green investing". This development involves the integration of Environmental, Social, and Governance (ESG) information into investment decisions. A significant advancement in the worldwide financial market is the integration of ESG (Environmental, Social, and Governance) data into investing choices. ESG ratings have emerged as a significant benchmark for investors in this scenario. However, there is now a considerable disparity in the rating outcomes provided by various rating agencies for particular companies. This disparity distorts the ratings and thus triggers exaggerated reactions from investors. This study investigates the influence of differences in ESG ratings on investor sentiment and its underlying mechanism using a sample of businesses listed on the A-share market in Shanghai and Shenzhen between 2015 and 2022. Research has shown that when there is a significant difference in ESG ratings, it has a detrimental effect on investor sentiment. This means that when there is a large divergence in ESG ratings, it negatively affects investor sentiment, leading to a decrease in their evaluation and confidence in the company. Empirical investigations demonstrate that the focus and consideration given by analysts and research reports play a crucial role in how differences in ESG ratings impact investor sentiment. Additional investigation reveals that the adoption of GRI standards and the verification of ESG reports by third-party entities can somewhat reduce the influence of divergence on the fluctuation of investor mood, as well as enhance investor acknowledgment of revealed information. The paper examines the influence of disagreement in ESG ratings on investor mood, contributes to existing research on ESG ratings dispute, and presents empirical evidence to support the development of China’s ESG ratings system and the establishment of a "rational" investment market.